'To spend is to choose': Des McConaghy and expenditure-based planning. Issue 6 (November 2019) - Long, Mark
Abstract : This article recovers the life and works of Des McConaghy (1931–2017), pioneer of expenditure-based planning for urban regeneration in the United Kingdom. Drawing on his experiences in Craigavon New Town, as director of the Shelter Neighbourhood Action Project in Liverpool, special advisor in the Department of the Environment and director of the Area Information Service, he developed an incisive critique of over-centralisation in the UK state, and proposed a novel form of two-tier fiscal programming, embedded in a local–central political framework, to drive forward concerted whole-of-government activity in targeted areas, restoring transparency and accountability to urban renewal.